2020
DOI: 10.1088/1757-899x/747/1/012076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the revision acetabular customized implant position by finite element modeling

Abstract: The article contains a biomechanical assessment of the performance of a customized endoprosthesis of the hip joint. Finite-element models of the hip bone and the implant in the projected and actual positions are prepared. The article provides the results of the static structural analysis for a patient in the two-leg standing position in the post-operative period. The results are compared for various implant positions. As a recommendation, it is proposed to optimize the location and the number of screws for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…According to the results of observations, it can be concluded that the pressure decreases with increasing distance. That's the way it should be when tested in a real environment [11].…”
Section: Modeling An Acoustic Field In Comsol Multiphysicsmentioning
confidence: 99%
“…According to the results of observations, it can be concluded that the pressure decreases with increasing distance. That's the way it should be when tested in a real environment [11].…”
Section: Modeling An Acoustic Field In Comsol Multiphysicsmentioning
confidence: 99%
“…Then dependences ( 10) and ( 11) are used to determine the lifting loads οY and profile drag loads οX acting on the blade section in the flow coordinate system [3,[4][5][6][7][8].…”
Section: Lifting Forces and Profile Drag Forces Determination Acting On The Blade Section In The Flow Coordinate Systemmentioning
confidence: 99%
“…However, it is much more expensive and time-consuming. Testing on simulation models, digital twins, virtual benches and digital platforms not just makes the development and verification of designed products cheaper [9]. It makes it possible, without making a physical prototype, to assess those parameters and processes that cannot be carried out on a physical model.…”
Section: Assessment Of the Passive Safety Of The Digital Twin In Frontal Impactmentioning
confidence: 99%